MEDICAL DISCOVERIES - Kavanaugh, Beatrice (Broomall, Pennsylvania : Mason Crest, 2017)
Medical science is advancing all the time. Researchers are constantly trying to find new ways to help people to have long and healthy lives. Thanks to their work, doctors today can cure diseases, lessen pain, replace unhealthy limbs or organs, and help infertile couples have children. Doctors can even keep seriously ill people alive against all odds. But not everyone is enamored with advances in medicine. They question whether it is appropriate to prolong life in all cases, or believe that certain treatments have been developed unethically. This book looks at how the ways that doctors treat the sick are developed, and examines some of the questions that are raised by advances in medical science.-- Source other than Library of Congress.
Introduction to health care -- Issues of new life -- Questions about the end of life -- The business of health care -- Moving toward the future.
Includes bibliographical references and index.
Keywords: Medical ethics -- Juvenile literature; Biothics -- Juvenile literature; Social medicine -- Juvenile literature; Medical ethics; Bioethics; Social medicine